2014
DOI: 10.5306/wjco.v5.i5.1097
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and natural history of breast cancer in younger Chinese women

Abstract: Younger patients in Hong Kong are more likely to encounter risk factors associated with breast cancer development and have more aggressive tumours than their older counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 32 publications
1
21
0
5
Order By: Relevance
“…In our series, this frequency was 24.42%, thus exceeding the frequency of the Occidental studies and concordant with the Maghreb studies. The average age of onset of breast cancer in the literature is often after 30 years (1,5,6) , which is consistent with our study with an average of 35.6 years. Several risk factors other than age are commonly associated with breast cancer in young women, including early menarche, nulliparity, first late pregnancy, and a family history of breast cancer.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In our series, this frequency was 24.42%, thus exceeding the frequency of the Occidental studies and concordant with the Maghreb studies. The average age of onset of breast cancer in the literature is often after 30 years (1,5,6) , which is consistent with our study with an average of 35.6 years. Several risk factors other than age are commonly associated with breast cancer in young women, including early menarche, nulliparity, first late pregnancy, and a family history of breast cancer.…”
Section: Discussionsupporting
confidence: 81%
“…In the pathological study, invasive breast carcinoma no special type is the most frequent histological type. It is all the more aggressive because it is associated with an SBR III grade, lymph node invasion, negative hormone receptors and overexpression of HER2 (1,4,5,6) . In our series, invasive breast carcinoma no special type was by far the most frequent (82.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mainly involve surgery followed by post-operative adjuvant therapies that may include chemotherapy, radiotherapy, endocrine therapy and/or targeted therapy. Although less than 15% of patients were reported to be diagnosed before age 40 [2], a higher proportion of these patients were subjected to adjuvant cytotoxic therapy [2].…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Anders et al, among women with early-stage breast cancer, younger patients were found to have larger tumors of higher grade, more lymph node positivity, lower estrogen receptor expression and higher HER2/neu overexpression, and eventually worse disease-free survival (DFS) 7. In a Chinese study, invasive breast cancer in younger patients was associated with more aggressive pathological features, such as a higher percentage of grade 3 histology, a higher proportion of tumors with lymphovascular invasion, and a more multifocal disease 8. On the other hand, a study conducted in Switzerland involving 2997 breast cancer patients assessed the impact of age at diagnosis on clinical presentation and other variables.…”
Section: Introductionmentioning
confidence: 99%